2014
DOI: 10.1038/ncomms6238
|View full text |Cite
|
Sign up to set email alerts
|

CD95 and CD95L promote and protect cancer stem cells

Abstract: CD95 (APO-1/Fas) is a death receptor used by immune cells to kill cancer cells through induction of apoptosis. However, the elimination of CD95 or its ligand, CD95L, from cancer cells results in death induced by CD95R/L elimination (DICE), a type of cell death that resembles a necrotic form of mitotic catastrophe suggesting that CD95 protects cancer cells from cell death. We now report that stimulation of CD95 on cancer cells or reducing miR-200c levels increases the number of cancer stem cells (CSCs), which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(104 citation statements)
references
References 49 publications
7
94
0
Order By: Relevance
“…However, this subpopulation of cells was still susceptible to etoposideinduced cell death caused by DNA strand breaks (47) and staurosporine-induced cell death caused by activating caspase 3 (48), suggesting that the surviving cells retain intact cell death pathways mediated by other stimuli. Our observation is consistent with a recent report that constant stimulation by CD95 of breast cancer, colon cancer, and renal cancer cells leads to a subpopulation of cells less sensitive to CD95-mediated apoptosis (20). When we performed a phenotypic analysis of the apoptosis-resistant SL-1 B lymphoma cells after prolonged anti-CD95 stimulation, we did not observe any phenotypic cell surface change, which is different from the recent finding that stimulation by CD95 can transform cancer cells into a more dedifferentiated state and converts apoptosis-resistant noncancer stem cells phenotypically into cancer stem cells (20).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…However, this subpopulation of cells was still susceptible to etoposideinduced cell death caused by DNA strand breaks (47) and staurosporine-induced cell death caused by activating caspase 3 (48), suggesting that the surviving cells retain intact cell death pathways mediated by other stimuli. Our observation is consistent with a recent report that constant stimulation by CD95 of breast cancer, colon cancer, and renal cancer cells leads to a subpopulation of cells less sensitive to CD95-mediated apoptosis (20). When we performed a phenotypic analysis of the apoptosis-resistant SL-1 B lymphoma cells after prolonged anti-CD95 stimulation, we did not observe any phenotypic cell surface change, which is different from the recent finding that stimulation by CD95 can transform cancer cells into a more dedifferentiated state and converts apoptosis-resistant noncancer stem cells phenotypically into cancer stem cells (20).…”
Section: Discussionsupporting
confidence: 82%
“…Our observation is consistent with a recent report that constant stimulation by CD95 of breast cancer, colon cancer, and renal cancer cells leads to a subpopulation of cells less sensitive to CD95-mediated apoptosis (20). When we performed a phenotypic analysis of the apoptosis-resistant SL-1 B lymphoma cells after prolonged anti-CD95 stimulation, we did not observe any phenotypic cell surface change, which is different from the recent finding that stimulation by CD95 can transform cancer cells into a more dedifferentiated state and converts apoptosis-resistant noncancer stem cells phenotypically into cancer stem cells (20). Thus, the mechanism underlying apoptosis resistance of SL-1 B lymphoma cells would be the other mode of regulation.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…A long noncoding RNA suppresses miR-34a by recruiting DNA methyl-transferase Dnmt3a via prohibitin-2 and histone deacetylase 1 (161). Dr. Marcus E. Peter (Northwestern University, Chicago, IL) reported that chronic stimulation of CD95 results in lower levels of miR-200c, monitored using a sensor plasmid for miR-200c, increasing the CD24 low stem-like population in breast cancer cells (22). This is driven by a type I interferon/STAT1 pathway (23).…”
Section: Clinical Trials Of Csc Targeting Therapeuticsmentioning
confidence: 99%